Collaborative Learning and Its Influence on English Reading Ability: A Study on the Eighth-Grade Students - Putri, Putri Azhari; Hastini; Sudarkam R. Mertosono; Darmawan (Institut Agama Islam Negeri Palopo, 2025)
The Effect of Collaborative Learning on the English Reading Ability of Grade VIII Students of SMPN 1 Sindue Tobata. Collaborative learning, which emphasizes student interaction and cooperation in achieving learning objectives, is hypothesized to improve reading comprehension and engagement. In this study, the researcher used purposive sampling, taking class VIII B with 20 students as the pre-experimental group. The results of data analysis showed that the average post-test score of students after being taught using collaborative learning (79.45) was higher than the pre-test score before being taught using collaborative learning (36.75). The findings revealed a significant increase in improving the English reading ability of eighth-grade students at SMPN 1 Sindue Tobata.